Missions and Cohesion Policy: Living separate or dancing together? - Francesco Cappellano; Francesco Molica; Teemu Makkonen (European Commission, Joint Research Centre (JRC), 2023)
This paper explores avenues for cross-fertilisation between the mission-oriented approach and Cohesion Policy. It argues in favour of mutual policy learning between the two to address some of their respective shortcomings: Cohesion Policy is facing a gradual erosion of its identity, whereas the mission-oriented approach needs a stronger territorial perspective. The mission-oriented approach could offer a theoretical blueprint for re-organizing Cohesion Policy priorities around few missions, linking more explicitly its objectives to major societal challenges so as to reinforce its rationale and revive its political ownership. Moreover, Cohesion Policy can draw inspiration from the concept of directionality to strengthen its result-orientation dimension. It should be also assessed whether the missions' blending of top-down and bottom-up approaches can inspire ideas to streamline the complex governance of Cohesion Policy. The mission-oriented approach can benefit from adopting Cohesion Policy peculiar architecture enabling joint broad priorities to be adapted to territorial contexts and into regional strategies. The mission-oriented approach could also learn from Cohesion Policy goal of maximising equity and efficiency, its focus on empowering regions, and its redistributive approach to foster the full potential of all EU regions to tackle societal challenges.
Keywords: 330; Cohesion policy; European Union; Mission-oriented approach; Policy learning; Regions